Promotion Mix to Increase Revenue in The Capital Hotel and Resort Restaurant in Badung Bali District - Ida Ayu Komang Juniansih; Komang Feby Kristiawan; Tettie Setiyarti; Ida Bagus Radendra Suastama (Profesional Muda Cendekia Publishing, 2020)
This study aims to determine the effect of the promotion mix and the variables that have a dominant influence on the income of The Capital Hotel and Resort restaurant for the period 2019. The sample of this study uses income from restaurants in The Capital Hotel and Resort and promotional costs for the period 2019. The data analysis technique used is multiple linear regression analysis, coefficient determination, F test and t test. The results showed that the results of the coefficient determination were 0.990, it could be said that the five independent variables contributed 99% to the income value, the F test results showed F count> F table (113.135> 3.97), which means that the five independent variables simultaneously had a positive effect and significant to the dependent variable. The t test results show t count (17,779)> t table (2,447) and its effect on the dependent variable (0,000 <0.005), stating that advertising (X1) is the variable that has the most dominant influence on income.